Serum lipidomic analysis identifies potential therapeutic targets for neurodegeneration - Zhang, Lumi; Li, Duanbin; Zhao, Na; Peng, Guoping (Frontiers in Human Neuroscience, 2025)
IntroductionCirculating very-long-chain saturated fatty acids (VLSFAs) may attenuate age-related cognitive decline, but their direct association with neurodegeneration biomarkers and the underlying mechanisms remain unclear.MethodsThis cross-sectional study examined associations between circulating fatty acid profiles, neurodegeneration (assessed by serum neurofilament light chain, NfL), cognitive function, and hypertension in 1,677 U.S. adults from the National Health and Nutrition Examination Survey (NHANES) 2013–2014. Advanced statistical methods including weighted quantile sum (WQS) regression, Bayesian kernel machine regression (BKMR), quantile g-computation (Qgcomp), and formal mediation analyses were employed.ResultsThe VLSFA mixture demonstrated significant inverse associations with serum NfL (β = −0.044, 95% CI: -0.076, -0.011) and the prevalence of hypertension (OR = 0.788, 95% CI: 0.672, 0.923). This association with NfL was non-linear, exhibiting a more pronounced protective effect at lower VLSFA concentrations. Higher VLSFA levels were significantly correlated with better cognitive performance, particularly in processing speed (Digit-Symbol Substitution Test) and memory (delayed recall). Hypertension was positively associated with NfL (β=4.133, 95% CI: 1.705, 6.562), an effect driven primarily by systolic blood pressure. Mediation analysis revealed that hypertension accounted for approximately 15–20% of the total association between VLSFAs and NfL.DiscussionCirculating VLSFAs are inversely associated with the neurodegeneration biomarker NfL and positively correlated with cognitive performance. This neuroprotective association appears to be partially mediated by blood pressure regulation pathways. These findings identify VLSFAs as a potential therapeutic target, warranting further longitudinal and interventional studies to confirm their role in mitigating neurodegeneration.